Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

For what integers $n$ does $\phi(2n) = \phi(n)$?

Could anyone help me start this problem off? I'm new to elementary number theory and such, and I can't really get a grasp of the totient function.

I know that $$\phi(n) = n\left(1-\frac1{p_1}\right)\left(1-\frac1{p_2}\right)\cdots\left(1-\dfrac1{p_k}\right)$$ but I don't know how to apply this to the problem. I also know that $$\phi(n) = (p_1^{a_1} - p_1^{a_1-1})(p_2^{a_2} - p_2^{a_2 - 1})\cdots$$


share|cite|improve this question

3 Answers 3

up vote 8 down vote accepted

Euler's $\phi $ function is multiplicative. More elaborately if for $a,b\in N$ with $(a,b)=1$ then $\phi (ab)=\phi (a)\phi (b)$. So let $n=2^km$ with $m$ being odd. Then we have if $k\ge 1$, $$\begin{align} \phi (n)&=\phi(2^k)\phi(m)=2^{k-1}\phi(m) \\ \phi(2n)&=\phi(2^{k+1})\phi(m)=2^{k}\phi(m)\end{align}$$ So $\phi (n)\ne \phi(2n)$. So $k<1\Rightarrow k=0\Rightarrow n$ must be odd.

Another easy proof: Let $n=2^k\prod_{i=1}^{n}p_i^{\alpha_i}$ with $k\ge 1$ and $2\ne p_i =$ primes, then we have $\phi (n)=\frac{n}{2}\prod_{i=1}^{n}(1-\frac{1}{p_i})$ and $\phi (2n)=\frac{2n}{2}\prod_{i=1}^{n}(1-\frac{1}{p_i})$.Can $\phi (n)$ be equal to $\phi(2n)$? Now consider $n=2k+1$ and find $\phi (n)$ and $\phi (2n)$. What do you see?

share|cite|improve this answer
I know that the function is multiplicitive, but I don't understand how to use that information. Sorry. – Ozera Jul 10 '13 at 15:46
I guess the 2nd proof will clear things up. – Abhra Abir Kundu Jul 10 '13 at 15:47
Actually I'm not really sure what it says, but I'm going to continue thinking about what the importance of it being multipicitive. – Ozera Jul 10 '13 at 15:56
Now is it clear @Ozera – Abhra Abir Kundu Jul 10 '13 at 16:08

Hint If $n$ is odd, then gcd$(n,2)=1$ thus

$$\phi(2n)=\phi(2) \phi(n) \,.$$

If $n$ is even, write $n=2^km$ with $m$ odd and $k \geq 1$.

$$\phi(n)=\phi(2^k) \phi(m) \,.$$ $$\phi(2n)=\phi(2^{k+1}) \phi(m) \,.$$

share|cite|improve this answer

Hint: You may also prove in general that


where $d=\gcd(m,n).$

share|cite|improve this answer
+1 Nice remarking the fact. :-) – Babak S. Aug 22 '13 at 7:36
The formula you gave is incorrect. It should have been $$\phi(mn) = \frac{d\phi(m)\phi(n)}{\phi(d)}$$ – Balarka Sen Jan 17 '14 at 15:32
Dear @BalarkaSen, yes, thanks for the correction. – Ehsan M. Kermani Jan 18 '14 at 20:15

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.